2019
DOI: 10.1002/app.48332
|View full text |Cite
|
Sign up to set email alerts
|

Novel CNC/silica hybrid as potential reinforcing filler for natural rubber compounds

Abstract: This work describes the development of a low‐density, renewable, and high reinforcing filler for natural rubber (NR) compounds. The cellulose nanocrystal (CNC)‐based hybrid filler was synthesized by decorating the surface of CNCs with silica using a simple and efficient coprecipitation method. The properties of the prepared hybrid were investigated by field emission scanning electron microscopy, Fourier transform infrared spectroscopy, X‐ray diffraction, nitrogen physisorption measurements, and Thermogravimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 66 publications
0
8
0
2
Order By: Relevance
“…With the growing need to find sustainable filler materials, research in the fillers domain becomes driven by the challenging task to make new fillers cope with previous technology performance levels . The filler morphology is another important research topic, and extensive work is being conducted on the use of anisotropic fillers based on silica, clay, or cellulose nanocrystals. Other strategies, not focusing on the filler itself, work around the opportunity to valorize waste as a usable resource for the tire industry .…”
Section: Introductionmentioning
confidence: 99%
“…With the growing need to find sustainable filler materials, research in the fillers domain becomes driven by the challenging task to make new fillers cope with previous technology performance levels . The filler morphology is another important research topic, and extensive work is being conducted on the use of anisotropic fillers based on silica, clay, or cellulose nanocrystals. Other strategies, not focusing on the filler itself, work around the opportunity to valorize waste as a usable resource for the tire industry .…”
Section: Introductionmentioning
confidence: 99%
“…Among the abundant kinds of fillers, carbon black (CB) is confirmed to be most efficient in reinforcing rubbers and, therefore, most widely used in the rubber industry. , However, the energy consumption in the manufacturing process and utilization of nonrenewable feedstock, i.e., the heavy hydrocarbons, for producing carbon black make it unsustainable. Also, the carbon footprint for making carbon black is tremendous due to the partial combustion of heavy hydrocarbons, which release over 2 tons of carbon dioxide for producing 1 ton of carbon black. , Therefore, alternative feedstock has been considered as substitutes for producing reinforcing filler of rubbers, especially the ones from potential recyclable waste materials and industrial/agriculture byproducts. Also, in some formulations of multifunctional elastomers, the total or partial replacement of conventional fillers (e.g., CB) with unconventional ones has been realized. On the other hand, studies on the reinforcement mechanism indicate that while the chemical nature of the fillers or additives, which determines the filler–rubber interaction, appears to be vital for reinforcing rubber composites, the size of the fillers or additives is also of prime importance in elastomer reinforcement. , It is suggested that any kind of fine particles with a desirable small size can reinforce rubbers . In this case, the abundant natural minerals may be another alternative way for providing substitutes of carbon black, which is important for utilization of natural resources and environmental friendliness. …”
Section: Introductionmentioning
confidence: 99%
“…The different surface energies of carbon black and silica prevent their hybrid fillers from forming a uniform filler network in rubber substrates, while the close combination and uniform distribution of carbon and silicon in the CSDPF can not only effectively avoid this problem, but also form a collaborative filler network 5,19 . Although many researchers have prepared CSDPFs by co‐precipitation or impregnation methods, the combination form and the distribution of the two phases in the new CSDPFs are still one of the key issue because the components and structural properties of carbon and silicon sources used are different 20,21 . In addition to the structure and components of filler itself, the surface modification can also directly affect the surface properties of filler 22,23 .…”
Section: Introductionmentioning
confidence: 99%